A graphene quantum dots based fluorescent sensor for anthrax biomarker detection and its size dependence1. Issue 24 (28th June 2015) - Ryu, Jaehoon; Lee, Eunwoo; Lee, Kisu; Jang, Jyongsik
<x xml:space="preserve">Abstract</x> Graphene quantum dots (GQDs) with two different diameters were modified via hybridization with a EuIII–macromolecule complex, and their application as dual emission fluorescent sensors for detection of Bacillus anthracis spores was investigated.